Reconstruction of massive post-sternotomy defects with allogeneic bone graft: four-year results and experience using the method - Kaláb, Martin; Karkoška, Jan; Kamínek, Milan; Matějková, Eva; Slaměníková, Zuzana; Klváček, Aleš; Šantavý, Petr (Interactive cardiovascular and thoracic surgery, 2016)
OBJECTIVES: Deep sternal wound infection poses a serious problem in cardiac surgery, with an up to 40% risk of mortality. Massive loss of sternum bone tissue and adjacent ribs results in major chest wall instability causing respiratory insufficiency and defects of soft tissue healing. Proposals for managing the situation have been published but the complexity of the issue precludes unequivocal resolution. Capitalizing on orthopaedic experience, we used allogeneic bone graft of sternum as a viable option. METHODS: We performed the transplantation of allogeneic bone graft in 10 patients. In 9 cases, an allograft of sternum was used and in 1 case an allograft of calva bone. After the primary cardiac surgery, a massive post-sternotomy defect of the chest wall had developed in all 10 patients. Vacuum wound drainage was applied in the treatment of all patients. To stabilize the transverse, titanium plates were used. Bone allograft was prepared by the official Tissue Centre. Crushed allogeneic spongy bone was applied to reinforce the line of contact of the graft and the edges of residual skeleton. In 9 cases, the soft tissue was closed by direct suture of mobilized pectoral flaps. In 1 case, V-Y transposition of pectoral flap was performed. RESULTS: In 6 cases, healing of the reconstructed chest wall occurred without further complications. In 3 cases, additional re-suture of the soft tissues and skin in the lower pole of the wound was necessary. Excellent chest wall stability along with the adjustment of respiratory insufficiency and good cosmetic effect was achieved in all cases. In 1 case, severe concomitant complications and no healing of the wound resulted in death within 6 months after the reconstruction. Median follow-up of all patients in the series was 14.1 months (1-36 months). In 4 patients, scintigraphy of the chest wall was performed. CONCLUSIONS: Our existing results show that allogeneic bone graft transplantation is a promising and easily applied method in the management of serious tissue loss in sternal dehiscence with favourable functional and cosmetic effects. The relatively small number of patients with such severe healing complications of sternotomy however puts critical limits to a more detailed comparison with other practices and evaluation of long-term results.
Keywords: mužské pohlaví; osteotomie; Male; senioři; senioři nad 80 let; výsledek terapie; šicí techniky; sternotomie; infekce chirurgické rány; Allogeneic bone graft of sternum; Female; Humans; Deep sternal wound infection; transplantace kostí; zákroky plastické chirurgie; pooperační komplikace; lidé; hojení ran; Bone Transplantation; Time Factors; Middle Aged; ženské pohlaví; lidé středního věku; reoperace; Postoperative Complications; Surgical Wound Infection; Wound Healing; Sternotomy; Aged, 80 and over; Pectoralis Muscles; prsní svaly; chirurgické laloky; Treatment Outcome; Osteotomy; homologní transplantace; Massive post-sternotomy defect; Reoperation; Surgical Flaps; Suture Techniques; dehiscence operační rány; časové faktory; Surgical Wound Dehiscence; Transplantation, Homologous; Aged; Plastic Surgery Procedures